Tridegin, a Novel Peptidic Inhibitor of Factor XIIIa from the Leech, Haementeria ghilianii, Enhances Fibrinolysis In Vitro - Seale, Lisa; Finney, Sarah; Sawyer, Roy T; Wallis, Robert B (Thrombosis and Haemostasis, 1997)
Tridegin is a potent inhibitor of factor Xllla from the leech, Haementeria ghilianii, which inhibits protein cross-linking. It modifies plasmin-mediated fibrin degradation as shown by the absence of D-dimer and approximately halves the time for fibrinolysis. Plasma clots formed in the presence of Tridegin lyse more rapidly when either streptokinase, tissue plasminogen activator or hementin is added 2 h after clot formation. The effect of Tridegin is markedly increased if clots are formed from platelet-rich plasma. Platelet-rich plasma clots are lysed much more slowly by the fibrinolytic enzymes used and if Tridegin is present, the rate of lysis returns almost to that of platelet- free clots. These studies indicate the important role of platelets in conferring resistance to commonly used fibrinolytic enzymes and suggest that protein cross-linking is an important step in this effect. Moreover they indicate that Tridegin, a small polypeptide, may have potential as an adjunct to thrombolytic therapy.